Da’wah and Environmental Conservation: An Analysis on Instagram - Risqi, Amadea; Risqy, Mukhammad; Ramadhani, Oktaviana; Imam Satrio, Diky (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2025)
Environmental issues are becoming increasingly complex global challenges, especially due to human actions that ignore the balance of nature. Environmental preaching in the context of digital media is important to see how Islamic values about ecology are communicated, accepted, and influence public awareness so that a flexible, innovative, and information technology-based approach strategy is needed to overcome the challenges of the current environmental crisis. This study aims to analyse the ecological preaching strategy carried out by the social media account @ecomasjid.id as an example of a religion-based communication strategy to increase social ecological awareness. The method used in this study is qualitative with a case study approach and literature study. Data were taken and collected from the content uploads of the Instagram account @ecomasjid.id such as captions, images, and video clips. The results of the study indicate that the environmental preaching strategy implemented by the Instagram account @ecomasjid.id is effective because it is in accordance with the theory of contemporary preaching strategies, namely that effective preaching must meet three main elements, namely the relevance of the social context, media that is in accordance with the characteristics of man, and a persuasive and aesthetic delivery style.